Global Drivers of and Local Resistance to French Shareholder Activism. Issue 1 (March 2014) - Girard, Carine; Gates, Stephen
<x xml:space="preserve">Abstract</x> Shareholder activism in France has made significant advances during the past 25 years even as it continues to face formidable sources of local resistance. But if the list of corporate governance improvements since 1989 described by the authors might lead one to conclude that France now has minority shareholder protection and shareholder activism comparable to those of the U.S. or U.K., powerful local interests, including much of French management, labor, and government, continue to mount effective resistance to such forces for change. The French government still works closely with French business elites and unions to manage both individual companies and the general economy. And government officials continue to speak publicly of "protecting" French firms from "illegitimate" foreign shareholders. Accordingly, the authors characterize French corporate governance as a "hybrid" model of shareholder activism, one that incorporates the perspectives and interests of the classic French stakeholder model as well as an emerging shareholder value movement. Although foreign institutional investors have increased their shareholdings in French companies and promoted "best practice" governance rules, particularly with respect to voting rights, local forces will continue to resist aggressive shareholder activism. Such a hybrid model makes the outcomes of shareholder activism less predictable, a risk that foreign investors and companies often respond to by seeking alliances with local proxy advisers and investor associations to gain "legitimacy."